Miocene-Pliocene strike-slip basin development along the Denali fault system in the eastern Alaska range: Chronostratigraphy and provenance of the Mccallum formation and implications for displacement - Allen, Wai K (Purdue University, 2016)
The Denali fault system represents one of the major strike-slip faults in North America but very little is known about the amount and timing of displacement on this 2000-km-long structure. The 7.9 M 2002 Denali Earthquake emphasized the importance of this fault system for understanding the deformational record of the upper plate of the southern Alaska convergent margin. Our analysis of the Miocene-Pliocene McCallum Formation located along the east-central part of the Denali fault provides one of the few records for Neogene displacement as well as changes in surface and basin processes related to tectonic transport. We have established a chronostratigraphic framework for the McCallum Formation that shows that it consists of a two-part stratigraphy that represents the progradation of alluvial-fan deposystems of an upper member over mainly lacustrine strata of a lower member. This upward coarsening progradational package has a minimum thickness of 564 m based on our measured stratigraphic sections. New ages from 40Ar/39Ar geochronology of tephras show that the lower member ranges in age from 6.1 to 5.07 Ma and that the upper member ranges from 5.03 to 3.80 Ma. U-Pb detrital zircon geochronology and 40Ar/39Ar detrital biotite ages from sandstone, and 40Ar/39Ar ages of volcanic clasts in conglomerate are all consistent with up to ∼ 230 km of dextral offset of the McCallum Formation from its sources of sediment on the opposite (east) side of the Denali and Totschunda fault systems. We present a minimum and maximum interpreted amount of displacement based on the new provenance data and modern displacement rates along the fault system. In both interpretations the McCallum basin would be located adjacent to the more northerly trending Totschunda fault in a transtensional setting during deposition of the lacustrine strata of the lower member. With strike-slip displacement of the McCallum basin, it was transported northward into a regional restraining bend. This stage of basin development was characterized by deposition of ...